2016
DOI: 10.1128/genomea.00247-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a γ-Hexachlorocyclohexane Degrader, Sphingobium sp. Strain TKS, Isolated from a γ-Hexachlorocyclohexane-Degrading Microbial Community

Abstract: Here, we report the complete genome sequence of a γ-hexachlorocyclohexane (γ-HCH) degrader, Sphingobium sp. strain TKS, which was isolated from a γ-HCH-degrading microbial community. The genome of TKS consists of two chromosomes and nine plasmids. The lin genes for conversion of γ-HCH to β-ketoadipate are dispersed on chromosome 1 and three out of the nine plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The GenoFinisher and AceFileViewer programmes were used to finish the sequencing completion 35 . More detailed information for these procedures have been published elsewhere 23 , 25 , 26 . Sequencing gap regions were amplified by PCR using KOD FX (TOYOBO) or Ex Taq (TaKaRa) by using the total DNA of the respective strains as templates, and the resultant DNA fragments were sequenced using primers for PCR amplification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GenoFinisher and AceFileViewer programmes were used to finish the sequencing completion 35 . More detailed information for these procedures have been published elsewhere 23 , 25 , 26 . Sequencing gap regions were amplified by PCR using KOD FX (TOYOBO) or Ex Taq (TaKaRa) by using the total DNA of the respective strains as templates, and the resultant DNA fragments were sequenced using primers for PCR amplification.…”
Section: Methodsmentioning
confidence: 99%
“…MI1205, 24 , 25 and Sphingobium sp. TKS, 26 were determined. On the basis of our comparison of the complete genome sequences of these three strains and UT26, in association with several supporting experimental data, the evolution of γ-HCH-degrading bacterial strains is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this hypothesis, pBBR_Pu_adhX for the expression of the adhX UT26 gene was introduced into three sphingomonad strains, Sphingobium sp. TKS [30], Sphingobium sp. MI1205 [31] and Sphingomonas sp.…”
Section: Identical or Almost Identical Adhx Orthologues Are Distributmentioning
confidence: 99%
“…Primary comparison of the genome sequences of sphingomonad strains including degraders of highly recalcitrant compounds supports the idea that sphingomonads are a versatile group because of the plasticity of their genomes (Nagata et al ., ; Aylward et al ., ). It is strongly suggested that plasmid‐mediated gene transfer and chromosome‐plasmid recombination, together with prophage and transposon‐mediated rearrangements, play prominent roles in the genome evolution of sphingomonads (Copley et al ., ; Nagata et al ., ; Tabata et al ., ,b,c; Hegedus et al ., ). In some cases, the gene organizations seem to be edited by using insertion sequences.…”
Section: Sphingomonads a Bacterial Group Containing Various Strains mentioning
confidence: 99%
“…MM‐1 from India (Tabata et al ., ; Tabata et al ., ), Sphingobium sp. TKS from Kyushu, Japan (Tabata et al ., ), and Sphingobium indicum B90A (Verma et al ., ). The genome organizations of these five lindane‐degrading strains are summarized in Table .…”
Section: Genomes Of Lindane‐degrading Sphingomonad Strainsmentioning
confidence: 99%